Math, asked by ABS111, 1 year ago

m=cab÷a-b,then b equals

Answers

Answered by JyotiYadav11
1
I think it will help you
Attachments:

vatsalbrainly: wrong
JyotiYadav11: I know that
vatsalbrainly: nice
JyotiYadav11: I didn't read the question carefully
vatsalbrainly: no problem...
vatsalbrainly: please follow me
vatsalbrainly: i will follow back
Answered by vatsalbrainly
1

m =  \frac{cab}{a - b}
m \times (a - b) = cab
 (a - b) =  \frac{cab}{m}
 - b =  \frac{cab}{m}  - a
 b =   - (\frac{cab}{m}  - a)
 b =   \frac{ - cab}{m}   +  a
Similar questions